Effect of dissolved oxygen on the oxidative and structural characteristics of protein in beer during forced ageing. (23rd November 2020) - Zong, Xuyan; Yang, Huirong; Jin, Xiaofan; Brennan, Charles S.; Coldea, Teodora Emilia; Cai, Linfei; Zhao, Haifeng
Summary: Oxygen is contributing to the deterioration of the beer and shortening the shelf‐life of the packaged product. The effect of dissolved oxygen (DO) on oxidative and structural characteristics of protein in beer during forced ageing was examined. Results showed that increased DO decreased obviously protein content in beer, and further reduced antioxidant activities of beer and lipid transfer protein 1 (LTP1). Meanwhile, the increase of DO decreased significantly the free thiol groups content and enhanced the disulfide bonds level in beer and LTP1. Results from circular dichroism, surface hydrophobicity and zeta‐potential illustrated that the increase of DO dramatically changed the secondary and tertiary structure of LTP1 with the decrease in the surface hydrophobicity, α‐helix and β‐turn contents, and the increase in the random coil and negative zeta potential. These results indicated that increased DO could damage the structure of LTP1 and had a negative impact on oxidative stability of beer. Abstract : Oxidative and structural characteristics of protein in beer.